Racial differences in the anatomy of the posterior fossa: neurosurgical considerations - Dao Trong, Huy Philip; Beynon, Christopher; Unterberg, Andreas; Schneider, Till M.; Jesser, Jessica (World neurosurgery, 2018)
Objective - Racial differences in anatomy of the cranium exist but have not been specifically considered in neurosurgical access planning. We sought to find differences in the anatomy of the posterior fossa in a cohort study consisting of Asian, African American, and Caucasian patients. - Methods - Magnetic resonance imaging data of 60 Asian, 57 African American, and 70 Caucasian individuals were obtained from the Human Connectome Project. Measurements were done in axial, coronal, and sagittal planes in T2-weighted thin-sliced images. P values were calculated using 2-tailed Student t test. P < 0.05 was considered significant. - Results - We measured distance in millimeters from the z values (craniocaudal axis) from the internal acoustic meatus to the transition of the transverse sinus into the sigmoid sinus. We discovered significant differences across all races. Our results show that the junction of the transverse to sigmoid sinus is lowest in Caucasians followed by Asians and African Americans. - Conclusions - Significant differences in anatomy have practical implications in the retrosigmoid approach to the cerebellopontine angle. Based on our findings, the junction of the transverse sinus with the sigmoid sinus can differ up to 0.5 cm in the craniocaudal axis depending on race. As neuronavigation is not standard to the approach to the cerebellopontine angle, the study aimed to provide the neurosurgeon operating in the retrosigmoid area additional knowledge to avoid sinus injury with subsequent complications, such as blood loss, sinus occlusion, or air embolism.
Gesehen am 31.05.2019